2019
DOI: 10.1007/s11469-019-00126-w
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Internet Gaming Disorder and Impulsivity: A Systematic Review of Literature

Abstract: Research examining Internet Gaming Disorder (IGD) has increased substantially over the past decade. One of the risk factors for IGD includes poor impulse control. The present study comprises the first ever systematic review of studies examining the relationship between IGD and impusivity utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. A literature search was conducted via EBSCO (which included the following academic databases: Academic Search Complete, Psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 99 publications
(284 reference statements)
4
72
0
1
Order By: Relevance
“…Previous studies have shown that impulsivity is associated with PVG [58,73]. In this context, Blinka, Škařupová and Mitterova [74] reported a positive relationship between PVG, game engagement, frequency of play, and dysfunctional impulsivity.…”
Section: Plos Onementioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have shown that impulsivity is associated with PVG [58,73]. In this context, Blinka, Škařupová and Mitterova [74] reported a positive relationship between PVG, game engagement, frequency of play, and dysfunctional impulsivity.…”
Section: Plos Onementioning
confidence: 83%
“…Taking into account the I-PACE model [15,16], it can be assumed that impulsivity is one of the crucial predictors of problematic behaviors. Additionally, many studies point to high impulsivity as one of the essential risk factors of psychoactive substance use [50][51][52] and behavioral addictions [53][54][55][56][57][58]. Previous studies have also indicated that high impulsivity is associated with low life satisfaction [27] and that addictions are also associated with low life satisfaction [59][60][61].…”
Section: Problematic Facebook Use and Problematic Video Gamingmentioning
confidence: 99%
“…The importance of self-control is even greater because previous studies have shown a positive relationship between self-control and success in various dimensions of life such as work, school, adjustment, interpersonal relationships, and management of problem desires ( De Ridder et al, 2012 ). Consequently, considering that previous studies have mostly focused on single aspects of selfcontrol ( Błachnio & Przepiorka, 2016 ; Kim et al, 2008 ; Khang et al, 2013 ; Mills & Allen, 2020 ; Şalvarlı & Griffiths, 2019 ) despite its multidimensionality (see Kotabe & Hofmann, 2015 ; Nęcka et al, 2016 ), further studies are needed to help explain the types of interdependence between various self-control dimensions and problematic behavior such as PFU and PVG.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is evidence supporting the therapeutic and health-related benefits of judicious gaming among adolescents and adults [ 8 ], excessive and disordered gaming can negatively affect gamers’ psychological, social, and physical health [ 9 ], further leading to the experience of functional impairments [ 10 ], chronic stress [ 11 ], and sleep disturbances [ 12 ]. With regards to cross-sectional associations, previous research has found several factors to be associated with IGD, including, but not limited to increased levels of anxiety, depression, stress [ 11 , 13 , 14 , 15 , 16 , 17 , 18 ], and impulsivity [ 19 , 20 ]. Additional personality traits have been associated with IGD, such as high levels of neuroticism and low levels of conscientiousness [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%